Novel bioactive Co-based alloy/FA nanocomposite for dental applications - Mohammadhossein Fathi; Mehdi Ahmadian; Mojgan Bahrami (Wolters Kluwer Medknow Publications, 2012)
Background: Dental cobalt base alloys are biocompatible dental materials and have been widely used in dentistry. However, metals are bioinert and may not present bioactivity in human body. Bioactivity is the especial ability to interact with human body and make a bonding to soft and hard tissues. The aim of the present research was fabrication and bioactivity evaluation of novel cobalt alloy/Fluorapatite nanocomposite (CoA/FaNC) with different amounts of Fluorapatite (FA) nanopowder. Materials and Methods: Co-Cr-Mo alloy (ASTM F75) powder was prepared and mixed in a planetary ball mill with different amounts of FA nanopowders (10, 15, 20% wt). Prepared composite powders were cold pressed and sintered at 1100°C for 4 h. X-ray diffraction (XRD), scanning electron microscopy and transition electron microscopy techniques were used for phase analysis, crystallite size determination of FA and also for phase analysis and evaluation of particle distribution of composites. Bioactivity behavior of prepared nanocomposites was evaluated in simulated body fluid (SBF) for 1 up to 28 days. Results: Results showed that nucleus of apatite were formed on the surface of the prepared CoA/FaNC during 1 up to 28 days immersion in the SBF solution. On the other hand, CoA/FaNC unlike Co-base alloy possessed bone-like apatite-formation ability. Conclusion: It was concluded that bioinert Co-Cr-Mo alloy could be successfully converted into bioactive nanocomposite by adding 10, 15, 20 wt% of FA nano particles.